Evaluation of zebu nellore cattle blood samples using the Cell-Dyn 3500 hematology analyzer - Borges, Alexandre Secorun [UNESP]; Amorim, Rogério Martins [UNESP]; Takahira, Regina Kiomi [UNESP]; Costa, Joselito Nunes; Alencar, Nayro Xavier; Peixoto, Ana Paula Cardoso; Kohayagawa, Aguemi [UNESP]; Kuchembuck, Marcio Rubens Graf [UNESP] (Universidade Federal de Goiás, 2014)
The Cell-dyn 3500 is a multiparameter flow cytometer, which may analyze samples from several species performing several simultaneous analyses. It is able to perform white blood cells, red blood cells and platelet counts, besides differential leukocyte counts, packed cell volume and hemoglobin determination. Cell-Dyn 3500 performs total leukocyte count both optically and by impedance. The equipment may choose one or other method, based on the reliability of the results. Erythrocyte and platelet counts are determined by impedance. Leukocyte differentiation is based on an optical principle, using separation in multiangular polarized light. The objective of this study was to compare the results of complete blood count of Zebu Nellore heifers from Cell-dyn 3500, with those obtained from a semi-automated cell counter (Celm CC 510) and the manual technique. Blood samples were collected from the jugular vein in 5 mL EDTA vacuum tubes from 58 Nellore heifers, at 24 months of age. Samples were processed in parallel in the three different techniques. Results were analyzed using paired t test, Pearson's correlation and the Bland-Altmann method. There was a strong correlation for all parameters analyzed by Cell-Dyn 3500, manual method and semi-automated cell counter, except for basophils and monocytes counts. These results confirm that this analyzer is reliable for blood samples analysis of zebu cattle.

O Cell-Dyn 3500 é um citômetro de fluxo multi-parâmetros que realiza várias análises simultâneas em diversas espécies de animais. Ele realiza a contagem total de leucócitos, de hemácias e de plaquetas, além do diferencial de leucócitos, o volume globular e a determinação de hemoglobina. O Cell-Dyn 3500 realiza a contagem total de leucócitos, tanto pelo método óptico quanto pela impedância. O equipamento pode escolher um ou outro método, baseado na confiabilidade dos resultados. A contagem de hemáceas e plaquetas é determinada pelo método de impedância. A diferenciação de leucócitos é baseada em um princípio óptico de análise, utilizando-se separação em luz polarizada multiangular. O objetivo deste trabalho foi comparar os resultados de hemogramas, realizados pelo Cell-Dyn 3500, com aqueles realizados por um contador celular semi-automático (Celm CC-510) e pela técnica manual. Amostras de sangue foram colhidas da veia jugular, em tubos de 5,0 ml à vácuo com EDTA, de 58 novilhas Nelore de 24 meses de idade. As amostras foram processadas paralelamente nas três técnicas. Os resultados foram analisados pelo teste t pareado, correlação de Pearson e pelo método de Bland-Altmann. Houve forte correlação entre os resultados hematológicos obtidos pelo Cell-Dyn 3500, pelo método manual e pelo contador celular semi-automático (Celm CC-510), exceto para a contagem de basófilos e monócitos. Esses resultados confirmam que o equipamento é confiável para a análise de amostras de sangue de gado zebuíno.
Avaliação de amostras de sangue de gado zebuíno nelore usando o analisador hematológico Cell-Dyn 3500
Keywords: CC-510; Cell-Dyn 3500; Hematology; Nellore; CC-150; Cell-Dyn 3500; Hematologia; Nelore